Identifying the processes and characterizing the pressure zone of water jet impacting on solid surface. (October 2022) - Zhang, Jianguo; Li, Xiyuan; Kou, Jianxin; Zhang, Di
The difficulty in understanding the flow characteristics of water jets impacting on solid surfaces made the water jet technology requiring further investigations. The Arbitrary Lagrange-Euler (ALE) method is used to develop a numerical model of the water jet impacting on a solid surface. It is also utilized in describing the flow characteristics of water and the pressure evolution in water during the impact process, understanding the formation mechanism of the pressure zone, and clarifying the influence factors of the stagnation pressure zone. The results showed that the pressure zone was characterized by the shock wave produced by the water jet impacting the solid surface. When the shock wave was contained in the water, it was the water hammer pressure stage. However, when the shock wave in water was disappeared, the stage was identified as the stagnation pressure. Besides, the water hammer pressure caused a high speed radial jet, and the stagnation pressure resulted in a low speed and stable radial jet. The stagnation pressure zone was the self-buffer zone of the water jet impacting the object, and the geometric characteristics of this zone were affected by the water jet diameter and the impact angle.